2023
DOI: 10.1093/eurheartj/ehad161
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics and lipidomics in atherosclerotic cardiovascular disease risk prediction

Abstract: Given the limited accuracy of clinically used risk scores such as the Systematic COronary Risk Evaluation 2 system and the Second Manifestations of ARTerial disease 2 risk scores, novel risk algorithms determining an individual’s susceptibility of future incident or recurrent atherosclerotic cardiovascular disease (ASCVD) risk are urgently needed. Due to major improvements in assay techniques, multimarker proteomic and lipidomic panels hold the promise to be reliably assessed in a high-throughput routine. Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…This could be explained by the short follow-up duration (24 weeks), low median age (32.00, IQR 27.00–37.00), and small sample size (44 patients). Furthermore, it has been demonstrated that conventional blood lipid analysis including that of LDL-C cannot encompass perturbations in overall lipid profiles and may not adequately assess the heterogeneity in interindividual atherogenic vulnerability [ 25 ]. In some cases, lower LDL-C may not be associated with improved cardiovascular outcomes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the short follow-up duration (24 weeks), low median age (32.00, IQR 27.00–37.00), and small sample size (44 patients). Furthermore, it has been demonstrated that conventional blood lipid analysis including that of LDL-C cannot encompass perturbations in overall lipid profiles and may not adequately assess the heterogeneity in interindividual atherogenic vulnerability [ 25 ]. In some cases, lower LDL-C may not be associated with improved cardiovascular outcomes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used proteomics to predict cardiovascular events (Helgason, et al, 2023), type II diabetes (Gadd, et al, 2023), and chronic kidney disease (Avram, 2023). Incorporating additional information, such as clinical (Williams, et al, 2022), lipidomics (Nurmohamed, et al, 2023), and metabolomics data (Nightingale Health Biobank Collaborative Group, et al, 2023) has been demonstrated to further enhance the predictive capabilities of disease risk. Apart from predicting disease risk, some machine learning models also excel in extracting in-depth insights of feature importance and individualized risk predictions from high-dimensional and complex datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, lipidomics offers a novel and powerful avenue to obtain a holistic analysis of the lipid profiles associated with atherosclerosis and a better understanding of the complex interaction between atherosclerosis and T1DM [11]. Thus, in the last years there has been an increased number of studies using lipidomics approaches that investigate the role of lipids in atherosclerotic CVD risk [12]. Among them, sphingolipids, and particularly ceramides, have been consistently found to be positively associated with ACS, CHF, or a vulnerable plaque phenotype [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the last years there has been an increased number of studies using lipidomics approaches that investigate the role of lipids in atherosclerotic CVD risk [12]. Among them, sphingolipids, and particularly ceramides, have been consistently found to be positively associated with ACS, CHF, or a vulnerable plaque phenotype [12,13]. A recent study performing a 1 H-NMR-derived lipidomics analysis in T1DM patients without CVD identified sphingomyelin as independently associated with carotid plaque presence, while w-6 fatty acids and linoleic acid were associated with a higher plaque burden [14].…”
Section: Introductionmentioning
confidence: 99%